Pengaruh E-Commerce, Budaya Organisasi, dan Pengetahuan Akuntansi terhadap Kinerja Usaha Mikro, Kecil, dan Menengah - Natsiruddin, Ahmad; Hasanah, Nuramalia; Armeliza, Diah (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
This study aims to determine the effect of the independent variable, namely E-Commerce,Organizational Culture, and Accounting Knowledge on the dependent variable, namely thePerformance of Micro, Small, and Medium Enterprises. The population of this study is MSMEs located in the Pulogadung Small Industry Center (PIK) area, East Jakarta. MSME performance is measured by e-commerce, organizational culture, and accounting knowledge. The samples obtained were 80 respondents with simple random sampling method. The results of this study indicate that e- commerce does not have a significant effect on the performance of MSMEs and organizational culture and accounting knowledge have a significant influence on the performance of MSMEs.